Stunting dan Indeks Massa Tubuh Anak Usia 0-5 Tahun - Elpira Asmin; Sri Wahyuni Djoko; Josepina Mainase (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Indonesia is one of the countries in Asia with the percentage of short toddlers besides Myanmar and Vietnam. Although Malaysia, Thailand, and Singapore have stunting cases, the stunting prevalence is less than 20 percent. Objective: To determine the prevalence of stunting and malnutrition in the work area of the Rumah Tiga Health Center. Methods: This study used a cross-sectional design with a total sample of 954 children under five. Result: the prevalence of stunting in children under five is 17.9 percent. The Body Mass Index of toddlers with a below-normal category is 4.82 percent. Conclusion: Toddlers who experience stunting occur at the age of 1-3 years and are dominated by males. Toddlers who have a body mass index below normal are also at the age of 1-3 years and are male.